The role of biodiversity in national parks on visitor experiences : a case study of Oulanka National Park in Finland and Golden Gate Highlands National Park in South Africa - Saarinen, J.J. (University of Pretoria, 2013)
Dissertation (MCom)--University of Pretoria, 2012.